Going Green Together: Effects of Green Transformational Leadership on Employee Green Behaviour and Environmental Performance in the Saudi Food Industry - Sobaih, Abu Elnasr E.; Hasanein, Ahmed; Gharbi, Hassane; Abu Elnasr, Ahmed E. (Agriculture (Basel), 2022)
Over the last few decades, environmental impacts have been a major concern not only for policymakers but also for scholars and leaders of organisations. The leadership of organisations can drive the green behaviour of their employees, thus driving the overall green performance of enterprises. In this research, we examined the direct influence of green transformational leadership (GTFL) on the environmental performance of food organisations and the indirect influence via green behaviour of employees. More specifically, we have examined the mediating effect of employee green behaviour, whether task-related or pro-environmental behaviour, on the association between GTFL and environmental performance. For this purpose, we adopted a pre-tested research instrument for data collection from 1050 employees in different food enterprises across the Kingdom of Saudi Arabia (KSA). We have used Amos structural equation modeling (SEM) to examine the direct and indirect effects of GTFL. The results confirmed a positive significant influence of GTFL on both dimensions of green behaviour, i.e., task-related and pro-environmental behaviour, and on environmental performance. The results showed a partial mediating effect of task-related behaviour in the link between GTFL and environmental performance, whereas pro-environmental behaviour has a perfect mediation effect. The results highlight the dynamic role of pro-environmental behaviour in affecting the above link and send a crucial message to leaders in the food industry about prioritizing pro-environmental behaviour when selecting and recruiting new employees. Additionally, development programs should be conducted to enhance the pro-environmental behaviours among employees.